1998
DOI: 10.1002/1529-0131(199806)41:6<986::aid-art5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Severe disturbance of the distribution and expression of type VI collagen chains in osteoarthritic articular cartilage

Abstract: Objective. The aim of this study was to evaluate the messenger RNA (mRNA) expression and distribution of the major pericellular type VI collagen in normal and osteoarthritic (OA) cartilage.Methods. Conventional and confocal laser scanning immunohistochemistry, as well as in situ hybridization experiments, were performed for all 3 collagen type VI chains in sections of normal and OA articular cartilage.Results. individual microfibrillar network in virtually all connective tissues (1-4). In hyaline articular car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 46 publications
5
40
0
1
Order By: Relevance
“…In contrast, MMP-1 was expressed only at very low levels in both normal (3) and OA articular chondrocytes in vivo. MMP-1 may be involved in the basic pericellular collagenous matrix turnover (36) that is found in both normal and OA cartilage (37). However, our data support previous indirect biochemical evidence (9) suggesting that MMP-1 is not primarily involved in interterritorial collagen breakdown in OA cartilage, although a role in disease stages that were not represented in our specimens cannot be excluded.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, MMP-1 was expressed only at very low levels in both normal (3) and OA articular chondrocytes in vivo. MMP-1 may be involved in the basic pericellular collagenous matrix turnover (36) that is found in both normal and OA cartilage (37). However, our data support previous indirect biochemical evidence (9) suggesting that MMP-1 is not primarily involved in interterritorial collagen breakdown in OA cartilage, although a role in disease stages that were not represented in our specimens cannot be excluded.…”
Section: Discussionsupporting
confidence: 76%
“…16,20 The few cells that did not stain positive for the investigated molecules, particularly in the osteoarthritic samples, might indicate individual damaged cells with aberrant gene expression pattern, which we have described for other genes as well. 24,28 Tissue culture studies confirmed that the ERK, JNK, p38, and NF-B pathways can be activated in articular chondrocytes as indicated by the presence of the phosphorylated isoforms or nuclear translocation of NF-B after IL-1␤ stimulation. These data confirm on the tissue level in vitro experiments using isolated chondrocytes as those performed in this and other studies.…”
Section: Discussionmentioning
confidence: 85%
“…24 Fluorochrome-labeled secondary antibodies (fluorescein isothiocyanate, Texas Red; and Cy-5, Dianova, Hamburg, Germany) were used for visualization of the antigens. Nuclear DNA was counterstained with propidium iodide.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 99%
“…(J Histochem Cytochem 57:923-931, 2009) K E Y W O R D S osteoarthritis cartilage ER stress bag-1 grp78 collagen VI NG2 OSTEOARTHRITIS (OA) IS A PROGRESSIVE DISEASE, with changes in chondrocyte gene expression and extracellular matrix (ECM) composition occurring before macroscopic structural damage is observed (Hamerman 1989). Articular chondrocytes in OA exhibit a hypermetabolic phenotype, with studies describing highly proliferative clonal chondrocytes, along with the upand downregulation of ECM molecules such as aggrecan (Matyas et al 1995), collagen II (Matyas et al 1995), perlecan (Tesche and Miosge 2004), metalloproteases (Mitchell et al 1996;Reboul et al 1996;Billinghurst et al 1997), aggrecanases (Lark et al 1997;Naito et al 2007), fibronectin (Wurster and Lust 1984;Brown and Jones 1990), collagen I (Deshmukh and Root 1974), and collagen VI (Hambach et al 1998;Pullig et al 1999). Etiologies ranging from genetic inheritance to trauma and aging can all contribute to the onset of OA, and further changes in gene expression occur as the disease progresses (Hardingham 2008).…”
mentioning
confidence: 99%